miR-221-3p and miR-222-3p regulate the SOCS3/STAT3 signaling pathway to downregulate the expression of NIS and reduce radiosensitivity in thyroid cancer - Ye, Ting (Exp Ther Med, 2021)
The expression levels of microRNA (miR)-221-3p and miR-222-3p in thyroid cancer have been found to be upregulated compared with those in normal tissues. The present study aimed to determine the effects and potential underlying mechanisms of miR-221-3p and miR-222-3p on the regulation of radioactive iodine ((131)I) uptake and radiosensitivity of thyroid cancer cells. The potential regulatory target genes of miR-221-3p and miR-222-3p were predicted by bioinformatics analysis, and reverse transcription-quantitative polymerase chain reaction was used to verify miR-221-3p, miR-222-3p and target gene expression levels in thyroid cancer tissues and cell lines. Overexpression of miR-221-3p or miR-222-3p in cell models was performed using lentivirus infection. Knockdown of miR-221-3p and miR-222-3p in cells was achieved using oligonucleotide inhibitor transfection. Western blotting was used to analyze the expression levels of target proteins. In addition, the effects of miR-221-3p and miR-222-3p on the radiosensitivity of thyroid cancer cells were verified using a colony formation assay. The results of the present study revealed that the expression levels of miR-221-3p and miR-222-3p were significantly upregulated, while the expression levels of suppressor of cytokine signaling 3 (SOCS3) were downregulated in thyroid cancer tissues. Furthermore, miR-221-3p and miR-222-3p overexpression downregulated the expression levels of SOCS3, E-cadherin and solute carrier family 5 member 5 (NIS), and upregulated the expression levels of phosphorylated STAT3 and vimentin. Following the overexpression of miR-221-3p or miR-222-3p in the FTC133 and TPC1 cell lines, their radiosensitivity was suppressed. In conclusion, the findings of the present study suggested that miR-221-3p and miR-222-3p may downregulate the expression levels of NIS and promote radioresistance. The potential mechanism was hypothesized to be associated with the miR-221-3p and miR-222-3p targeting of the SOCS3 gene, which may subsequently activate the STAT3 signaling pathway.